A Literature Review: Faktor Pendidikan Wiraswasta, Lingkungan dan E-Commerce terhadap Minat Berwiraswasta - Irawan, Hengki; Azwarudiansyah, Febri; Ekawati, Farida (STIES ALIFA, 2024)
Entrepreneurial interest is a person's attitude that shows interest in certain things without any coercion or persuasion. Someone who has an interest in entrepreneurship means that he is ready for the risks and uncertainties in the climate or process of whether the business is successful or not. Several factors cause the emergence of entrepreneurial interest. Entrepreneurship education factors, environment and e-commerce are factors that are often discussed by several previous studies. This research method is qualitative with library research. Its nature is a literature review. The results of the study showed the influence of entrepreneurship education on entrepreneurial interest. In entrepreneurship education, individuals are taught about the mentality and mindset of maturity to be skilled and create their own businesses so that they can create new jobs for the surrounding environment. The environment influences entrepreneurial interest. In the environment where a person lives, a mindset and attitude will be formed. The environment is a supporting factor given to someone to generate entrepreneurial interest. E-commerce also influences entrepreneurial interest. E-commerce offers a form of ease of buying and selling. So many people are interested in buying and selling from e-commerce.